Dynamic Marketing Strategy in Responding to Changes in Consumer Behavior during the Work from Home Era - Eti Rahmawati; Iis Mariam; Rousdy Tamba; Nurhayati (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
The shift to Work from Home (WFH) practices has altered consumer behavior patterns and created new challenges for firms in adjusting their marketing approaches. This study examines how dynamic marketing strategy affects marketing effectiveness in the context of behavioral changes among WFH workers in Bandung City. A quantitative associative approach was employed using survey data collected from 120 formal sector employees who had implemented WFH for at least six months. Data were gathered through structured questionnaires and analyzed using multiple linear regression. The findings indicate that dynamic marketing strategy exerts a positive and significant effect on marketing effectiveness (β = 0.512) (p < 0.05). In contrast, changes in consumer behavior demonstrate a negative and significant impact when not properly anticipated (β = −0.287) (p < 0.05). The model explains 51.3% of the variance in marketing effectiveness. These results emphasize the importance of adaptive marketing capabilities, particularly market sensing and organizational agility, in responding to evolving consumer behavior patterns.